Co-production of Nisin and γ-Aminobutyric Acid by Engineered Lactococcus lactis for Potential Application in Food Preservation - Liu, Jiaheng; Meng, Furong; Du, Yuhui; Nelson, Edwina; Zhao, Guangrong; Zhu, Hongji; Caiyin, Qinggele; Zhang, Zhijun; Qiao, Jianjun (Frontiers in Microbiology, 2020)
Microbiological contamination and oxidative damage are the two main challenges in maintaining quality and improving shelf-life of foods. Here, we developed a Lactococcus lactis fermentation system that could simultaneously produce nisin, an antimicrobial peptide, and γ-aminobutyric acid (GABA), an antioxidant agent. In this system, we metabolically engineered a nisin producing strain L. lactis F44 for GABA production by expression of glutamate decarboxylase and glutamate/GABA antiporter. GABA biosynthesis could facilitate nisin production through enhancing acid resistance of the strain. By applying a two-stage pH-control fermentation strategy, the engineered strain yielded up to 9.12 g/L GABA, which was 2.2 times higher than that of pH-constant fermentation. Furthermore, we demonstrated the potential application of the freeze-dried fermentation product as a preservative to improve the storage performance of meat and fruit. These results suggested that the fermentation product of nisin-GABA co-producing strain could serve as a cost-effective, easily prepared and high-performance food preservative.